Paneth-like cells disruption and intestinal dysbiosis in the development of enterocolitis in an iatrogenic rectosigmoid hypoganglionosis rat model - Budianto, Iskandar Rahardjo; Kusmardi, Kusmardi; Maulana, Andi Muh.; Arumugam, Somasundaram; Afrin, Rejina; Soetikno, Vivian (Frontiers in Surgery, 2024)
BackgroundHypoganglionosis resembles Hirschsprung disease (HSCR) which is characterized by severe constipation. Enterocolitis due to hypoganglionosis or Hirschsprung-associated enterocolitis (HAEC) is a life-threatening complication of both diseases. This study investigated the role of Paneth-like cells (PLCs) and gut microbiota in the development of enterocolitis in an iatrogenic rectosigmoid hypoganglionosis rat model.MethodsThe rectosigmoid serosa of male Sprague-Dawley rats were exposed to 0.1% benzalkonium chloride (BAC). The rats were then sacrificed after 1, 3, 5, 8, and 12 weeks. A sham group was sacrificed on Week 12. With hematoxylin-eosin staining, the ganglionic cells were quantified, the degree of enterocolitis was analyzed, and the PLCs was identified. Intestinal barrier function was assessed for the anti-peripherin, occludin, and acetylcholinesterase (AChE)/butyrylcholinesterase (BChE) ratio. qRT-PCR was used as reference for the evaluation of antimicrobial peptide (AMP) of PLCs using cryptdins, secretory Phospholipase A2, and lysozyme levels. 16S rRNA high-throughput sequencing on fecal samples was performed to analyze the changes in the intestinal microbiota diversity in each group.ResultsAfter 1 week of intervention, the ganglion cells were fewer in all sacrificial 0.1% BAC groups at varying times than those in the sham group. Occludin and peripherin were decreased, while the AChE/BChE ratio was increased. At Week 5 postintervention, the number of α-defensins-positive PLCs increased in the sigmoid colon tissues from BAC-treated rats. Conversely, PLCs-produced AMP decreased from Week 5 to Week 12. The sham group demonstrated increased Lactobacillus and decreased Bacteroides, while the 0.1% BAC group exhibited reciprocal changes, indicating dysbiosis. Enterocolitis occurred from Week 1 postintervention.ConclusionApplication with BAC influences the disruption of PLCs in Week 5 postintervention, and dysbiosis exacerbate the occurrence of enterocolitis. Further research on Paneth cells involvement in HAEC development is warranted.